2004
DOI: 10.1080/j.1440-1614.2004.01488.x
|View full text |Cite
|
Sign up to set email alerts
|

Disability and Service use among Homeless People Living with Psychotic Disorders

Abstract: Despite high levels of contact with a well-organized, sectorized mental health service in an affluent country, this pocket of several hundred people had high levels of persisting disability and needs. The literature and local experience suggest that changing this situation is likely to require co-ordinated policy and practice between the health, welfare and housing sectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 36 publications
2
31
0
1
Order By: Relevance
“…The prevalence of co-morbidity in the homeless population is significantly higher than it is for the general population. This finding applies equally in Australia as in other countries and across different time periods and different homeless sub-populations (see, e.g., Koegel et al 1988;Fischer & Breakey 1991;Jablensky et al 1999;Teesson et al 2000;Herrman et al 2004;Teeson et al 2004;Fazel et al 2008;Flatau et al 2010Flatau et al , 2012.…”
Section: Introductionmentioning
confidence: 90%
“…The prevalence of co-morbidity in the homeless population is significantly higher than it is for the general population. This finding applies equally in Australia as in other countries and across different time periods and different homeless sub-populations (see, e.g., Koegel et al 1988;Fischer & Breakey 1991;Jablensky et al 1999;Teesson et al 2000;Herrman et al 2004;Teeson et al 2004;Fazel et al 2008;Flatau et al 2010Flatau et al , 2012.…”
Section: Introductionmentioning
confidence: 90%
“…This phenomenon of "transinstitutionalisation" may be multifactorial in aetiology [48]. Herrman et al (2004) reported a higher lifetime prevalence of psychotic disorders among people living in marginal accommodation in Melbourne compared with ten years earlier. The shrinking supply of accommodation of this type was noted which may have resulted in a greater concentration of residents with psychotic disorders who were the least able to find alternative accommodation, perhaps leading to their reinstitutionalisation [49].…”
Section: Recent Studies Of Outcomes Of Community Mental Health Carementioning
confidence: 98%
“…3,10 In general, homeless persons have more difficulty accessing services. 4,11 Thus, although addiction treatment has a positive impact on the overall health of homeless persons affected by co-occurring disorders, 12 access is more difficult for the homeless that are affected with relatively more serious mental disorders compared to other homeless people. 13 Grella and Stein 14 examined the outcomes of individuals (80% of whom had been homeless) with co-occurring disorders who received drug treatment in programs that varied in their integration of mental health services.…”
Section: Introductionmentioning
confidence: 98%
“…3 Indeed, Herrman et al have found that addiction problems were present in 40% of homeless men and 20% of homeless women. 4 Studies on mental health service utilization show that a substantial proportion of users are homeless. Research has estimated that the proportion of homeless persons using emergency psychiatric services is between 15% 5 and 21%, 6 and seriously mentally ill persons using these services are usually very resistant to and noncompliant with the treatments provided.…”
Section: Introductionmentioning
confidence: 99%